Advances in energy transfer processes : proceedings of the 16th course of the International School of Atomic and Molecular Spectroscopy : Erice, Sicily, Italy, 17 June-1 July, 1999 - Di Bartolo, Baldassare; Chen, Xuesheng (Science and culture series (River Edge, N.J.). Spectroscopy., 2001)
This book describes advances in both experimental and theoretical treatments in the field of energy transfer processes that are relevant to various fields, such as spectroscopy, laser technology, phosphors, artificial solar energy conversion, and photobiology. It presents the principles and available techniques through specific examples. In addition, it examines current and possible applications, including the most recent developments, and projects future advances and research possibilities in the field.